Faketing of Evidence of Tax Invoice That Has Damage to State Revenue (Number : 131/Pid.Sus/2018/PT SMG) - Indri Aprianti; Muhamad Eko Nuralam; M Taufik Hidayatullah; Putri Erna Oktavia; Yuni Wulandari (Westscience Press, 2023)
The term fictitious tax invoice is also known as an illegitimate tax invoice. According to the Director General of Taxes Circular Number 32/PJ/2010, an invalid tax invoice is a tax invoice that is not based on an actual transaction, and is issued by an entrepreneur who has not been confirmed as a taxable entrepreneur. The term fictitious tax invoice is also known as an illegitimate tax invoice. According to the Director General of Taxes Circular Number 32/PJ/2010, an invalid tax invoice is a tax invoice that is not based on an actual transaction, and is issued by an entrepreneur who has not been confirmed as a taxable entrepreneur. Tax Criminal Case in Blitar District Court Decision No. 556/Pid.B/2013/PN. Found in the indictment given the element of forgery of tax invoices committed by the Defendant, For this reason, according to the author, it is necessary to explain the indictment. The results of the analysis from the authors of the paper stated that in this tax invoice falsification case, the judge's decision against the defendant was considered wise and appropriate but different from the public prosecutor in fact it was still not in accordance with the case.